What could have been done? : Investigating missed opportunities for differentiation in EFL teaching - Maryani (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
Differentiated instruction has gained particular attention in English as Foreign Language (EFL) teaching trends. EFL teachers have put some effort into infusing differentiation into their classrooms; therefore, according to previous research, the implementation of differentiated instruction by EFL teachers in the classroom remains lacking. This study explored missed opportunities for differentiation, defined as instances where teachers had the chance to apply differentiation but failed or even refused to do so. Through a qualitative case study design, the data were collected from three sessions of classroom observation and semi-structured interview with one EFL teacher. After careful data analysis through data condensation, data display, and conclusion, the findings revealed that the three components of differentiated instruction in the observed classroom, such as content, process, and product, were largely absent. There was indeed little observed attempt by the teacher to process differentiation; however, it appeared limited. The differentiation is underrepresented, mainly due to time constraints and the teacher’s lack of ability to tailor the content, process, and product to students’ readiness, interests, and learning profiles. Furthermore, this research identified other factors contributing to the missing opportunities, including limited resources, inadequate teaching experiences, and classroom management issues. The study suggests several strategies to address the missed opportunities for differentiation and provides other recommendations for teachers’ improvement.